Odpowiedź :
Odpowiedź:
a) m = 4
b) m = 2
Szczegółowe wyjaśnienie:
a) (x³ - 2x² -23x + 60) : (x - m) = ( x² + 2x -15)
Pomnóżmy:
(x - m) · ( x² + 2x -15) = x³ + 2x² - 15x - mx² - 2mx + 15m
Zredukujmy:
x³ + (2 - m)x² - (15 + 2m)x - 15m
Porównajmy:
x³ + (2 - m)x² - (15 + 2m)x - 15m = x³ - 2x² -23x + 60
Współczynniki muszą być równe, a więc:
2 - m = -2 ⇒ m = 4
-(15 + 2m) = -23 ⇒ -15 - 2m = - 23 ⇒ 2m = 8 ⇒ m = 4
15m = 60 ⇒ m = 4
Odp.: m = 4
b) x³ - x² - x - 15 = (x² + mx + 5)(x - 3)
Pomnóżmy:
(x² + mx + 5)(x - 3) = x³ - 3x² + mx² - 3mx +5x -15
Zredukujmy:
x³ - (3 -m)x² - (3m - 5)x - 15
Porównajmy:
x³ - (3 - m)x² - (3m - 5)x - 15 = x³ - x² - x - 15
Współczynniki muszą być równe, a więc:
- (3 - m) = -1 ⇒ -3 + m = - 1 ⇒ m = 2
-(3m - 5) = -1 ⇒ -3m + 5 = - 1 ⇒ m = 2
Odp.: m = 2
I wszystko jasne
Pozdrawiam